Investigating the effect of the marker assortment size distribution and fabric width on the fabric use efficiency - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2015)
Using the inputs of the production system efficiently is one of the most important factors to increase the competitiveness of the companies. Increasing efficiency of the fabric usage which is one of the most sufficient inputs of the ready-made garment production, decreasing the product cost. Factors which affect the fabric usage efficiency are placement of the garment patterns to the marker plan, fabric width and size distribution of marker assortment. In this study, effect of the size distribution of marker assortment and the fabric width on the fabric usage efficiency was investigated. For the application processes, 24 different fabrics width were obtained for (from) 4 different size distributions and totally 96 marker plans were prepared. By analyzing the prepared marker plans, fabric usage ratios were obtained and the effect of the fabric width and the assortment distribution on the fabric usage efficiency was investigated.
Keywords: efficiency; fabric usage efficiency; marker plan; fabric width; assortment distribution